Coating of AISI 1010 Steel by Ni-WC Using Plasma Transferred Arc Process - Tosun, Gul (Springer Heidelberg, 2014)
In the present study, mixed powders of 95% Ni and 5% WC were coated on the surface of AISI 1010 steel by plasma transferred arc process. The effect of current variation on the microstructure and hardness of the alloyed surfaces was investigated. After deposition, microstructural analyses including metallographic examination and microhardness measurements of the coatings were performed. The alloyed surfaces showed an increase in hardness when current was increased and this was attributed to the formation of hard phases. Upon solidification of the coating, different microstructures formed depending on the processing parameters. The microstructures of the alloyed surfaces consisted of widmanstatten ferrite, grain boundary ferrite, acicular ferrite, bainite and martensite.
Keywords: Composite materials; Microstructure; Hardness